2021
DOI: 10.48550/arxiv.2102.01391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian Neural Networks for Virtual Flow Metering: An Empirical Study

Bjarne Grimstad,
Mathilde Hotvedt,
Anders T. Sandnes
et al.

Abstract: Recent works have presented promising results from the application of machine learning (ML) to the modeling of flow rates in oil and gas wells. The encouraging results combined with advantageous properties of ML models, such as computationally cheap evaluation and ease of calibration to new data, have sparked optimism for the development of data-driven virtual flow meters (VFMs). We contribute to this development by presenting a probabilistic VFM based on a Bayesian neural network. We consider homoscedastic an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This may lead to a biased estimate of the model's predictive performance in future process conditions. In fact, in Grimstad et al (2021), data-driven virtual flow meters were developed for a diverse set of 60 wells from five petroleum assets and it was shown that data-driven VFMs may yield adequate predictions of historical flow rates but not necessarily for future flow rates. As a result, Grimstad et al (2021) motivates for use of other approaches, such as gray-box VFMs.…”
Section: Mechanistic and Data-driven Modelsmentioning
confidence: 99%

On gray-box modeling for virtual flow metering

Hotvedt,
Grimstad,
Ljungquist
et al. 2021
Preprint
Self Cite
“…This may lead to a biased estimate of the model's predictive performance in future process conditions. In fact, in Grimstad et al (2021), data-driven virtual flow meters were developed for a diverse set of 60 wells from five petroleum assets and it was shown that data-driven VFMs may yield adequate predictions of historical flow rates but not necessarily for future flow rates. As a result, Grimstad et al (2021) motivates for use of other approaches, such as gray-box VFMs.…”
Section: Mechanistic and Data-driven Modelsmentioning
confidence: 99%

On gray-box modeling for virtual flow metering

Hotvedt,
Grimstad,
Ljungquist
et al. 2021
Preprint
Self Cite